2018
DOI: 10.1002/etep.2697
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive fractional-order PID control of PMSG-based wind energy conversion system for MPPT using linear observers

Abstract: Summary This paper designs a novel adaptive fractional‐order PID (AFOPID) control of a permanent magnetic synchronous generator (PMSG)‐based wind energy conversion system, which attempts to extract the maximum wind power by using a linear perturbation observer. The combinatorial effect of generator nonlinearities and parameter uncertainties, unmodelled dynamics, and stochastic wind speed variation is aggregated into a perturbation, which is then estimated in real time by a linear extended‐state observer called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…On the other hand, fractional-order control theories and applications of traditional integer-order and fractional-order systems have attracted increasing attention over the past two decades [24]. The fractional-order PI/PID control algorithm has been considered as one of the most widely and successfully used methods in complex systems, such as servo systems [25,26], a nonlinear vertical tank system [27], electric balance vehicle system [28], an induction motor drive system [29], permanent magnetic synchronous generator [30], automatic voltage regulator systems [31], single-area delayed power systems [32], and multi-area interconnected power systems [33]. One particular concern is the fractional-order frequency control of an isolated microgrid.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, fractional-order control theories and applications of traditional integer-order and fractional-order systems have attracted increasing attention over the past two decades [24]. The fractional-order PI/PID control algorithm has been considered as one of the most widely and successfully used methods in complex systems, such as servo systems [25,26], a nonlinear vertical tank system [27], electric balance vehicle system [28], an induction motor drive system [29], permanent magnetic synchronous generator [30], automatic voltage regulator systems [31], single-area delayed power systems [32], and multi-area interconnected power systems [33]. One particular concern is the fractional-order frequency control of an isolated microgrid.…”
Section: Introductionmentioning
confidence: 99%
“…where k 12 , k 13 , k 22 , and k 23 are positive tuning parameters and sat(·) is the saturation function, which is defined as…”
Section: Fosmc Designmentioning
confidence: 99%
“…Nevertheless, the chattering phenomenon limits the implementation of SMC in practice. To tackle the issue, fractional‐order sliding mode control (FOSMC) is proposed based on the integration of SMC method and fractional‐order calculus theory . Different from integer‐order rational transfer functions, the fractional‐order operator possesses the infinite memory and takes into consideration the whole history of input signals, which effectively reduces the chattering phenomenon of conventional SMC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors proposed a particle swarm optimization (PSO) tuned adaptive fractional order PID (AFOPID) controller based MPPT method and concluded that the performance of the proposed MPPT method is better as compared to the PID, FOPID, and fuzzy in terms of convergence time, fitness function value and IAE. 30 The proposed AFOPID MPPT method uses a d component of stator current and rotor speed for the steady-state error compensation. However, the overall MPPT approach can be improved by reducing the complexity and computational sensor requirement.…”
Section: Introductionmentioning
confidence: 99%